2021
DOI: 10.2196/26011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Disordered Eating Behavior: Qualitative Analysis of Social Media Posts

Abstract: Background A growing body of evidence is suggesting a significant association between the COVID-19 pandemic and population-level mental health. Study findings suggest that individuals with a lifetime history of disordered eating behavior may be negatively affected by COVID-19–related anxiety, and prevention measures may disrupt daily functioning and limit access to treatment. However, data describing the influence of the COVID-19 pandemic on disordered eating behaviors are limited, and most finding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 34 publications
2
41
0
3
Order By: Relevance
“…This study investigated the impact of COVID‐19 on young women's risk of developing an eating disorder and the effectiveness of active interventions during COVID‐19. Findings suggest that during COVID, disordered eating behaviors and negative affect were significantly higher than pre‐COVID levels, which echoed findings from qualitative research (Brown et al, 2021; Nutley et al, 2021; Richardson et al, 2020). Significant difference in disordered eating pre‐versus during COVID remained when adjusting for negative affect.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This study investigated the impact of COVID‐19 on young women's risk of developing an eating disorder and the effectiveness of active interventions during COVID‐19. Findings suggest that during COVID, disordered eating behaviors and negative affect were significantly higher than pre‐COVID levels, which echoed findings from qualitative research (Brown et al, 2021; Nutley et al, 2021; Richardson et al, 2020). Significant difference in disordered eating pre‐versus during COVID remained when adjusting for negative affect.…”
Section: Discussionsupporting
confidence: 66%
“…Using retrospective reporting, Phillipou et al (2020) found that a general population in Australia increased their restricting and binge eating behaviors during COVID‐19, whereas those who had an ED history increased not only their restricting, binge eating but also purging and exercise behaviors. Qualitative retrospective research has found that those who experienced disordered eating tend to report similar themes; an increase in ED symptoms, need for help and support, limited access to services during COVID‐19 (Brown et al, 2021; Nutley et al, 2021; Richardson, Patton, Phillips, & Paslakis, 2020). To date only one study has used a prospective design to report on the impact of COVID on disordered eating, where college students in the US recorded no significant change in weight, BMI, or BMI category, between January and April 2020, but over this time the subjective descriptions of weight changed to significantly be more likely to fall into a higher category (Keel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it could also reflect a genuine effort by users to learn about ED treatments or exchange views on recovery from EDs. A willingness among users of ED communities on Reddit to foster healthier habits and attempt recovery from EDs during the first months of the pandemic was also noted in another study [28]. The increase in discussions could have also been caused by users debating or inquiring about alternatives for their interrupted ED treatments such as self-management of recovery or anonymous helplines [9,17].…”
Section: Principal Findingsmentioning
confidence: 71%
“…As a consequence, people with EDs, or those at-risk for developing an ED, could be reaching out to these communities during the COVID-19 pandemic to receive the social support they are lacking in their everyday life. A qualitative study on three ED communities on the social media website Reddit during the first months of the COVID-19 pandemic uncovered themes such as increased ED symptomatology, changes in daily routine, and treatment interruptions [ 28 ], which echo issues that were also found in survey studies.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies suggest differential outcomes based on eating disorder (ED) type (e.g, anorexia nervosa vs binge eating), 6 persons with histories of (ED) may be particularly affected by pandemicrelated stressors, exacerbating risk for recurrence or elevated severity of their ED and worsening symptoms. [6][7][8][9][10][11][12] Preliminary studies examining disordered eating behaviors (DEB) during the COVID-19 pandemic cautioned how lockdown may exacerbate problematic eating behaviors, [13][14][15] and that ED may shape COVID-19 risk. 16 In an Italian community sample collected at two different phases of Italy's pandemic lockdown, Cecchetto et al 17 found that depression and anxiety were associated with emotional eating, and that stress was associated with binge eating.…”
Section: Disordered Eating Behavior Eating Disorders and Covid-19mentioning
confidence: 99%